Analysis and Assessment of Wind Energy Potential of Socotra Archipelago in Yemen - Almekhlafi, Murad A. A.; Al-Wesabi, Fahd N.; Khan, Imran; Nemri, Nadhem; Mahmood, Khalid; Mahgoub, Hany; Negm, Noha; El-Kustaban, Amin M.; Zahary, Ammar (Tech Science Press, 2022)
The increasing use of fossil fuels has a significant impact on the environment and ecosystem, which increases the rate of pollution. Given the high potential of renewable energy sources in Yemen and the absence of similar studies in the region, this study aims to examine the potential of wind energy in Socotra Island. This was done by analyzing and evaluating wind properties, determining available energy density, calculating wind energy extracted at different altitudes, and then computing the capacity factor for a number of wind turbines and determining the best. The average wind speed in Socotra Island was obtained from the Civil Aviation and Meteorology Authority data, only for the five-year data currently available. The results showed high wind speeds from June to September (9.85-14.88 m/s) while the wind speed decreased for the rest of the year. The average wind speed in the five years was 7.95 m/s. The average annual wind speed, wind energy density, and annual energy density were calculated at different altitudes (10, 30, and 50 m). According to the International Wind Energy Rating criteria, the region of Socotra Island falls under Category 7 and is classified as Superb for most of the year. This study provides useful information for developing wind energy and an efficient wind approach.